2016
DOI: 10.1007/164_2016_5004
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Non-canonical Cyclic Nucleotides: Hydrolysis and Transport

Abstract: This chapter addresses cNMP hydrolysis by phosphodiesterases (PDEs) and export by multidrug resistance associated proteins (MRPs). Both mechanisms are well-established for the canonical cNMPs, cAMP, and cGMP. Increasing evidence shows that non-canonical cNMPs (specifically cCMP, cUMP) are also PDE and MRP substrates. Hydrolysis of cUMP is achieved by PDE 3A, 3B, and 9A, which possibly explains the cUMP-degrading activities previously reported for heart, adipose tissue, and brain. Regarding cCMP, the only known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Cyclic cytidine monophosphate (cCMP) and cyclic uridine monophosphate (cUMP) are synthesized by soluble guanylate and soluble adenylate cyclases in mammalian systems, although an as-yetto-be identified generator likely accounts for the majority of production given the dissociation between sGC/sAC and cCMP/cUMP expression patterns (9). ExoY, a bacterial nucleotidyl cyclase, is known to generate cUMP in non-mammalian systems (7). Hydrolysis of cCMP is catalyzed by PDE7A whereas cUMP is broken down by PDE3A, PDE3B and PDE9A (7).…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic cytidine monophosphate (cCMP) and cyclic uridine monophosphate (cUMP) are synthesized by soluble guanylate and soluble adenylate cyclases in mammalian systems, although an as-yetto-be identified generator likely accounts for the majority of production given the dissociation between sGC/sAC and cCMP/cUMP expression patterns (9). ExoY, a bacterial nucleotidyl cyclase, is known to generate cUMP in non-mammalian systems (7). Hydrolysis of cCMP is catalyzed by PDE7A whereas cUMP is broken down by PDE3A, PDE3B and PDE9A (7).…”
Section: Challengesmentioning
confidence: 99%
“…ExoY, a bacterial nucleotidyl cyclase, is known to generate cUMP in non-mammalian systems (7). Hydrolysis of cCMP is catalyzed by PDE7A whereas cUMP is broken down by PDE3A, PDE3B and PDE9A (7). Functionally both nucleotides have been shown to activate PKA/PKG (287), cyclic nucleotide gated channels (288), and cCMP is described as a partial agonist of EPAC (289).…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular cGMP is reduced through the degradation by phosphodiesterases or through extracellular export via multidrug resistanceassociated proteins (MRPs). 28 Phosphodiesterase 1 expression has been found to be increased in neointimal lesions in human coronary arteries. 4 In addition, an upregulated MRP4 and MRP5 expression has also been shown in human atherosclerotic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PDE2 and PDE3, whose activity may be modulated by cGMP, are also involved in NO and NP signaling. More recently, it was also demonstrated that PDEs are able to cleave non-canonical cNMPs (in particular, cCMP and cUMP) in addition to hydrolyzing the canonical cNMPs, cAMP, and cGMP (Schneider and Seifert 2017) which may broaden the therapeutic impact of PDE inhibitors in the future. In recent years, it turned out that PDE inhibition provides effective treatment approaches in various diseases (Baillie et al 2019).…”
Section: Cgmp Pde Structure and Functionmentioning
confidence: 99%